Incidence of the teacher’s metaphorical discourse in the teaching of the complex number concept (2018)
In this paper, it is presented two math teachers’ discourse analysis results, to identify the possible incidence of the metaphorical language used by them, in the learning of the concept of a complex number with ninth grade students. The analysis of the metaphorical language of the teacher is done in the light of the Cognitive Theory of Mathematics. It seeks the understanding of mathematics in the metaphorical thinking of people, and not in the rigorous demonstrations of books, emphasizing the connection that has the body with the cognitive processes, inducing the main key for the reform of teaching and learning processes focused on mathematical communication.